Evolution of occupational illness in Spain during 2009-2020: Territorial and industrial trends - Delgado-Sánchez, Dayana (2023)
This study analyzes the temporal evolution of occupational illnesses and their causing agents in Spain during the period 2009-2020, paying close attention to territorial and industrial trends. Similar to the case of work accidents, results suggest a positive association between the state of the economic cycle and the incidence rate of occupational illnesses. The reported increase in occupational illnesses between 2009 and 2020 should not be interpreted as bad news. Regulatory changes underwent by Spain’s government introduced a logical harmonization in illnesses’ notification criteria, which led to a temporal convergence of occupational illnesses with and without work leave days. Also, legal reforms facilitated the updating of the list of occupational illnesses and their causing agents, which constitutes a sign that the level of protection of Spanish workers improved, in terms of occupational health and safety at the workplace